Upper Paleolithic human remains from Šandalja cave, Istria, Croatia - Janković, Ivor (Array, 2009)
Excavations at Šandalja Cave during the 1960's yielded thirty-seven human skeletal fragments from the middle portion of the c. 12, 300 BP Epigravettian "B" level. Very few human remains of this age are known from south-central Europe, and, thus, the Šandalja sample has the potential to inform us about the biology of the last Ice Age peoples of this region. Although a preliminary description of many of the specimens was published in 1972, a more thorough treatment of these remains is warranted. The present work offers a detailed descriptive and comparative analysis of all of the remains. The project addresses the taphonomy and demographics of the sample. Furthermore, issues of how terminal Pleistocene south-Central Europeans are related to and how they may have been adaptively different from earlier and later peoples are addressed through analyses of Upper Paleolithic, Mesolithic, and more recent comparative samples. Taphonomically, the Šandalja remains are very fragmentary and are unlikely to have been from burials. Demographically, the sample represents at least two adult individuals, with at least one female. Comparatively, the Šandalja remains are notable for their gracility. Sizes of seven of the eight teeth fall significantly below Upper Paleolithic and Mesolithic averages. The one supraorbital specimen exhibits browridge metrics well below Upper Paleolithic and Neolithic averages, and the shape of the browridge as well as its size is more similar to that seen in recent Europeans.